Aid Supplies Over Time: Addressing Heterogeneity, Trends, and Dynamics. (May 2015) - Jones, Sam
Summary: What determines how much foreign aid donors provide? Existing answers to this question point to a complex range of influences. However, the tasks of distinguishing between long- and short-run factors, as well as differences between donors, have not been adequately addressed. Taking advantage of data spanning nearly 50 years, this paper uses panel cointegration techniques to consider these issues. The analysis provides clear evidence for heterogeneity both between donors and over time, bandwagon effects, and a growing influence of security considerations in aid provision. Domestic macroeconomic shocks have a moderate but delayed effect on aid disbursements.